PERAN BRAND AWARENESS MEMEDIASI PENGARUH SOCIAL MEDIA MARKETING TERHADAP PURCHASE INTENTION (Studi Pada Calon Konsumen Bron Cafe di Kota Denpasar) - Triaksara, Komang Bagus Cahya; Ekawati, Ni Wayan; Rastini, Ni Made (Buletin Studi Ekonomi; VOLUME.29.NO.02.TAHUN.2024DO - 10.24843/BSE.2024.v29.i02.p04, 2024)
The purpose of this study aims to explain the role of brand awareness in mediating the influence of social media marketing on purchase intention. This research was conducted at Bron Café Denpasar. Samples were taken from as many as 110 respondents through the purposive sampling method and distributed using a Google form questionnaire with adjusted criteria. Measured with 11 indicators and using a Likert scale. The method of determining the sample used in this research is non-probability sampling, namely the purposive sampling technique. The analysis technique uses path analysis (path analysis Sobel test and variance is accounted for the test. The results of this study indicate that all hypotheses are accepted. Social media marketing has a positive and significant effect on purchase intention. Social media marketing has a positive and significant influence on brand awareness. Brand awareness has a positive and significant effect on purchase intention. Social media marketing has a positive and significant effect on purchase intention.